From Biomass‐Derived Furans to Aromatics with Ethanol over Zeolite. (6th October 2016) - Teixeira, Ivo F.; Lo, Benedict T. W.; Kostetskyy, Pavlo; Stamatakis, Michail; Ye, Lin; Tang, Chiu C.; Mpourmpakis, Giannis; Tsang, Shik Chi Edman
Abstract: We report a novel catalytic conversion of biomass‐derived furans and alcohols to aromatics over zeolite catalysts. Aromatics are formed via Diels–Alder cycloaddition with ethylene, which is produced in situ from ethanol dehydration. The use of liquid ethanol instead of gaseous ethylene, as the source of dienophile in this one‐pot synthesis, makes the aromatics production much simpler and renewable, circumventing the use of ethylene at high pressure. More importantly, both our experiments and theoretical studies demonstrate that the use of ethanol instead of ethylene, results in significantly higher rates and higher selectivity to aromatics, due to lower activation barriers over the solid acid sites. Synchrotron‐diffraction experiments and proton‐affinity calculations clearly suggest that a preferred protonation of ethanol over the furan is a key step facilitating the Diels–Alder and dehydration reactions in the acid sites of the zeolite.